Testing the applicability of tagging the Great crested newt (Triturus cristatus) using passive integrated transponders - Weber, Lukáš; Šmejkal, Marek; Bartoň, Daniel; Rulík, Martin (PloS one, 2019)
Tracking individual animals with small-sized passive integrated transponder tags (PIT tags) has become a popular and widespread method, one which can be used for investigating life history traits, including dispersal patterns of small protected animals such as newts. In this study, we tested the applicability of PIT tag usage for individual marking with the Great crested newt (Triturus cristatus) as a model amphibian species, and to test the detection of the newts in nature using a passive telemetry system. Clove oil was used as an anaesthetic before surgery. We implanted PIT tags under the skin of 140 newts. The survival rate of newts was 98.57%. X-ray images were taken to check the exact positions of the PIT tags. Since approximately 15.71% of the newts were capable of expelling the tag from their bodies, tag loss has to be accounted for in future behavioural studies dealing with newts and other amphibians potentially capable of frequent tag expulsion. Lastly, we detected by passive telemetry 97 individuals out of 100 released into a natural breeding pond. Males had higher activity (13 detected males vs 7 females per hour) than females, thus males could be detected if present with more certainty. The result of the movement behaviour showed that e.g. the male of T. cristatus in a breeding pond can travel up to 20 m in 78 seconds. In summary, this promising method could allow the automatic data collection of marked newts in aquatic as well as in terrestrial biotopes, providing data on their dispersal, diurnal activity and movement behaviour.
Keywords: rybníky; chování zvířat; Telemetry; Female; technologie dálkového snímání; zvířata; Remote Sensing Technology; identifikace na rádiové frekvenci - prostředky; Ponds; ženské pohlaví; telemetrie; Male; Radio Frequency Identification Device; Triturus; Czech Republic; Animals; Česká republika; mužské pohlaví; Behavior, Animal